A Historical–Legal Perspective on the Constitution of the First French Republic and Executive Power in the Second French Republic - Rapajic, Milan M.; Spalević, Žaklina S. (Collection of Papers of the Faculty of Philosophy in Priština, 2026)
In the history of French republicanism, five republics have been established, each differing in duration, institutional structure, and the types of political systems they introduced. A notable feature of the Constitution of 1793, which proclaimed the Republic one and indivisible, is that it never entered into force. Its significance lies in the abolition of the census-based electoral system and the introduction of universal suffrage. The organs of power provided for by this Constitution included the National Assembly, the Executive Council, the heads of republican administrative bodies, and the Court of Cassation. The revolutionaries were guided by noble but at the same time highly radical ideas. This is particularly reflected in the strongly democratic conception of the organization of the legislative branch. The Constitution is often described as establishing a weak government subordinate to the legislature, a legislature subordinate to the people, and the people as the ultimate sovereign over their representatives and judges of their work. This formulation represents a concise summary of the Constitution of 1793.It took fifty-five years for the Second Republic to be established after the First Republic inaugurated by the Constitution of 1793, following the Revolution of 1848. LouisNapoléon Bonaparte, nephew of Napoleon Bonaparte, was elected the first president in direct elections for a four-year term. In public discourse, he was referred to as the “PrincePresident.” Thus, for the first time in the history of French republican constitutionalism, the head of state emerged as a distinct constitutional organ. The President of the Republic held significant powers. For example, he had the right to submit draft legislation to the National Assembly through ministers, as well as to oversee and ensure the implementation of laws. Formally, he was the supreme commander of the armed forces. Relations between the President and the National Assembly were regulated by the President’s obligation to submit annual reports on the general state of affairs of the Republic to the Assembly. In the field of foreign relations, the head of state was empowered to conduct negotiations and conclude treaties, subject to ratification.In its constitutional history, France has experimented with almost all systems of executive power organization, as briefly outlined in this paper. This raises the question of what kind of executive power system was established in the Second French Republic. Our conclusion is that it represented a specific form of mixed regime, in which the constitutional drafters appear to have taken the American presidential system as a model. However, the short duration of the Second Republic—closely linked to the single presidential mandate of the head of state as the sole executive authority—prevents a fully precise determination of the legal nature of this constitutional and political system. A clearer understanding of its institutional framework would require a longer period of political practice, including the exercise of the presidential function by multiple officeholders. Thus, the Second Republic is often regarded primarily as a transitional political framework that ultimately paved the way for the establishment of an authoritarian regime in monarchical form under its first republican head of state, who later became the last French emperor.
Keywords: Сonstitution; First French Republic; Second French Republic; executive power